Efficacy of some bacteria in the control of growth and citrinin productionby Penicillium citrinum - S.M. REDDY, P. GIRIDHAR and (Indian Phytopathology, 2002)
The efficacy of some saprophytic bacteria in the control of growth and production of the mycotoxin citrinin by P. citrinum, was investigated. P. aeruginosa and Klebsiella sp. completely inhibited the growth of P. citrinum in liquid culture when both bacteria and fungus were inoculated simultaneously. The growth and citrinin production was also inhibited by Escherichia coli and Xanthomonas citri to a considerable extent. When P. citrinum was inoculated 5 days before bacteria, a significant amount ofcitrinin was produced. It is suggested that P. aeruginosa can be exploited in the biocontrol of P. citrinum infestation and citrinin production as it inhibited the growth and citrinin production even when it was inoculated 5 days after P. citrinum inoculation.